Geometrical quaternionic coupling for three dimensional wave equations - Borges Neto, Manoel Ferreira [UNESP]; Marão, José Antonio Pires; Costa, Felix; Coelho, J. C. (Academic Publications, 2014)
The present work has the scope to show the relationship between four three-dimensional waves. This fact will be made in the form of coupling, using for it the Cauchy-Riemann conditions for quaternionic functions [#!BorgesZeMarcio!#], through certain Laplace's equation in [#!MaraoBorgesLP!#]. The coupling will relate those functions that determine the wave as well as their respective propagation speeds.
Keywords: coupling, coupling wave equations in three dimensional space